Lyme Disease : Why It's Spreading, How It Makes You Sick, and What to Do about It - Barbour, Alan G., 1946- (Book collections on Project MUSE., 2015)
An expert on tick-borne diseases, Alan G. Barbour explains the course of illness that results from infection, diagnosis and treatment options, and steps that can be taken to avoid a tick bite in the first place. The ticks that transmit Lyme disease may also transmit other disease-causing pathogens, and these other infections are considered as well.